Geochemical investigations of northern Norwegian fjord sediments - Sources and spatial variability of marine and terrigenous components - Canzler, Lea Philine (UiT Norges arktiske universitet, 2016)
Fjords represent unique coastal marine environments with high sedimentation rates. They can be used for intensive investigations focusing on geochemical, mineralogical, biological, and sedimentological processes. In this study I investigate 42 surface sediment samples from the outer and inner parts of the Vestfjord, Ofotfjord, Tysfjord and tributary fjord arms in northern Norway. Samples were analysed for their bulk elemental composition, grain size distribution, and total carbon and nitrogen contents (Ctot, Ntot). Furthermore, total organic and inorganic carbon and nitrogen concentrations (Corg, Cinorg, Norg and Ninorg) as well as the carbon and nitrogen isotopes (δ13C, δ15N) were analysed. The measurements were performed to identify geochemical proxies for the contribution of terrestrial organic matter (TOM) versus marine organic matter (MOM) into the fjords. The results indicate a sedimentary environment characterized by an overall dominant contribution of MOM compared to the relatively small input of terrestrial derived material. The extremely high supply of MOM is presented by Corg/Norg ratios ranging between 6 and 10, stable carbon isotope values (δ13Corg) between -24‰ and -21‰, and stable organic nitrogen (δ15Norg) signatures that vary between 4.7‰ and 6.9‰. The terrigenous material content is in general extraordinary low, and TOM increases from the outer part of the Vestfjord towards the innermost fjord parts of the Ofotfjord and Tysfjord. A correlation between δ13Corg and δ15Norg and the Corg/Norg ratios indicates high influences of marine derived OM. In addition, marine primary productivity is found to be the main contributor of calcium carbonate (CaCO3). CaCO3 increases towards the outer fjord parts and can be used to identify carbonate aquatic productivity by marine organisms and potentially trace the variable and relatively strong inflow of Atlantic water masses. Numerous proxies as those described above can be used to develop a better understanding of environmental processes since fjord sediments ...